Northward dispersal of dinosaurs from Gondwana to Greenland at the mid-Norian (215–212 Ma, Late Triassic) dip in atmospheric pCO2 - Kent, Dennis V.; Clemmensen, Lars B. (2021)
The earliest dinosaurs (theropods and sauropodomorphs) are found in fossiliferous early Late Triassic strata dated to about 230 million years ago (Ma), mainly in northwestern Argentina and southern Brazil in the Southern Hemisphere temperate belt of what was Gondwana in Pangea. Sauropodomorphs, which are not known for the entire Triassic in then tropical North America, eventually appear 15 million years later in the Northern Hemi- sphere temperate belt of Laurasia. The Pangea supercontinent was traversable in principle by terrestrial vertebrates, so the main barrier to be surmounted for dispersal between hemispheres was likely to be climatic; in particular, the intense aridity of tropical desert belts and unstable climate in the equatorial humid belt accompanying high atmospheric pCO2 that characterized the Late Triassic. We revisited the chronostratigraphy of the dinosaur- bearing Fleming Fjord Group of central East Greenland and, with additional data, produced a correlation of a detailed magnetostra- tigraphy from more than 325 m of composite section from two field areas to the age-calibrated astrochronostratigraphic polarity time scale. This age model places the earliest occurrence of sauro- podomorphs (Plateosaurus) in their northernmost range to ∼214 Ma. The timing is within the 215 to 212 Ma (mid-Norian) window of a major, robust dip in atmospheric pCO2 of uncertain origin but which may have resulted in sufficiently lowered climate barriers that facilitated the initial major dispersal of the herbivorous sau- ropodomorphs to the temperate belt of the Northern Hemisphere. Indications are that carnivorous theropods may have had dis- persals that were less subject to the same climate constraints.